Renovación urbana integral de un sector de la ciudad consistente en los tres cementerios antiguos y sus zonas aledañas en el municipio de Palmira, Valle del Cauca. - Parra Osorio, Jessica; Ortiz Figueroa, Marlen Dayana (Universidad Antonio Nariño, 2021)
The urban change causes a transformation according to many of the many needs that are generated in all areas that may arise, according to this urban dynamics are created within these sectors, neighborhoods and communities in general, which over time go from declining to improve in these situations, presenting in them a number of conflicts of occupation, regulations and uses, which have a social and physical deterioration, In the case of sector 13 in the city of Palmira-Valle, the objective of this work is to generate a proposal for the integral urban renewal of a central sector of Palmira, which includes the three old cemeteries and their surroundings, which will allow highlighting the patrimonial and historical elements as collective memory of the place and at the same time integrate through the public space the existing and proposed housing and equipment in the area to be intervened.